The development of web-based learning environment to enhance students’ numeracy and reasoning - Adelia, Viona; Putri, Ratu Ilma Indra; Zulkardi; Doorman, Michiel (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Despite the growing emphasis on numeracy as a critical outcome of mathematics education, many instructional approaches fail to connect numeracy learning with students’ reasoning development in meaningful ways. Existing research has not sufficiently explored the integration of technology-supported environments for fostering numeracy through theoretically grounded task design. Addressing this gap, the present study introduces a novel web-based learning environment grounded in numeracy theory and task design principles aimed at enhancing students' numeracy competence and mathematical reasoning. The development and implementation process involved iterative trials with 25 fifth-grade students: a one-to-one trial (n = 2), a small-group trial (n = 5), and a field trial (n = 18). Data were collected from students’ written responses on the web-based platform and their oral explanations. Findings demonstrate that the developed environment meets three key criteria: validity, as it aligns with relevant theoretical and empirical foundations; practicality, based on its usability and feasibility for students; and effectiveness, as evidenced by improved reasoning skills. These results highlight the potential of well-designed web-based learning environments to meaningfully support the development of numeracy competence while simultaneously fostering mathematical reasoning in primary education.